2021
DOI: 10.1186/s42834-020-00076-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessing air pollution tolerance of plant species in vegetation traffic barriers in Kathmandu Valley, Nepal

Abstract: Vegetation traffic barriers along roads can be an effective structure to improve roadside air quality and to reduce human exposure to traffic air pollutants. However, the selection of the plant species should be considered as an important design parameter for vegetation traffic barriers because different plant species demonstrate different levels of tolerance to air pollutants. This study compares the air pollution tolerance of different plant species found in the vegetation traffic barriers in the Kathmandu v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 44 publications
0
24
1
Order By: Relevance
“…Pandey et al (2015) recorded APTI values of 16.9 and 26.0 for M. indica and F. benghalensis, respectively. In contrast, Shrestha et al (2021) recorded F. Benjamina as sensitive species with an APTI value = 6.3 compared to 5.8 in the present study.…”
Section: Assessment Of Apti and Apicontrasting
confidence: 99%
“…Pandey et al (2015) recorded APTI values of 16.9 and 26.0 for M. indica and F. benghalensis, respectively. In contrast, Shrestha et al (2021) recorded F. Benjamina as sensitive species with an APTI value = 6.3 compared to 5.8 in the present study.…”
Section: Assessment Of Apti and Apicontrasting
confidence: 99%
“…Loss in chlorophyll content in plants is due to suspended particulate matter and other pollutants in the air, as reported by Tripathi and Gautam 25 . It can be observed that lower chlorophyll content in both plants indicates a higher sensitive nature of the plant species towards air pollution 26 .…”
Section: No 2 Concentrationmentioning
confidence: 96%
“…In addition, the ability of other plant species apart from the abovementioned was previously reviewed and reported by other researchers [32,[97][98][99][100]. The APTI of the same plant or different plants varies from place to place based on different air pollution levels, seasons, climatic variation, and other environmental factors, such as temperature and humidity [25,101,102]. The socio-economic parameter and APTI of the 28 plant species reviewed for pollution assimilation were subjected to a grading scale to determine the anticipated performance of plant species [60].…”
Section: Assessment Of Air Pollution Using Apti and Apimentioning
confidence: 99%